BOOK REVIEW: UNDERSTANDING SECOND LANGUAGE ACQUISITION - Dey, Manna (LLT Journal: A Journal on Language and Language Teaching, 2023)
Lourdes Ortega's "Understanding Second Language Acquisition" was first published by Routledge in 2008. Lourdes Ortega is an internationally renowned scholar in the field of second language acquisition and applied linguistics. Her work has been instrumental in advancing our understanding of the learning and acquisition of second languages. Lourdes Ortega’s Understanding Second Language Acquisition is an excellent resource for anyone interested in the study of second language acquisition (SLA). The book provides an in-depth exploration of the key concepts of SLA and offers a comprehensive overview of current research, theories, and approaches. It is a valuable resource for both language educators and students alike.